Bench‐Stable Electrophilic Indole and Pyrrole Reagents: Serendipitous Discovery and Use in C–H Functionalization. Issue 12 (15th December 2017) - Caramenti, Paola; Waser, Jerome
Abstract : The development of reagents allowing the reversal of the standard reactivity (Umpolung) of small building blocks is an important field of research in chemistry, as it allows increasing the flexibility of organic synthesis. Indoles and pyrroles are ubiquitous heterocycles in natural products and drugs. They are usually functionalized making use of their high nucleophilicity. In contrast, only few methods are based on the use of electrophilic indole and pyrrole synthons, as the needed reagents are highly unstable or can be used only with a very narrow scope. Herein, we report the serendipitous discovery and first use in the C–H functionalization of arenes of IndoleBX and PyrroleBX, new thermally highly stable benziodoxol(on)e hypervalent iodine reagents. IndoleBX and PyrroleBX could be obtained in one step from the corresponding heterocycles and acetoxy benziodoxolone using a Lewis acid catalyst. The mild reactions conditions allowed the introduction of a broad range of functional groups, including ethers, halogens and boronic esters. The new reagents could then be used in the rhodium‐ and ruthenium‐catalyzed C–H heteroarylation of arene rings bearing heterocyclic or benzamide directing groups. Such transformations could not be realized using previously reported C–H functionalization procedures. Abstract :